The Use Of A Cell-Free Synthesis System For The Study Of Factor FVIII - Heath, P R; Malia, R G; Tomlinson, S; Preston, F E (Thrombosis and Haemostasis, 1981)
There is good evidence that FVIIIR:Ag is synthesized by endothelial cells but the site of synthesis of FVIII:C and the precise biochemical relationship between the various components of the factor VIII complex remains obscure. In order to study the biosynthesis of porcine factor VIII we have established a cell-free synthesis system based on a wheatgerm lysate wherein exogenous messenger R.N.A’s extracted from cultured porcine endothelial cells are used to direct protein synthesis in vitro. Preliminary biosynthetic labelling experiments confirmed that, using our recently described IRMA assay, the cultured cells synthesized and secreted FVIIIR:Ag. mRNA was extracted from lg cultured porcine endothelial cells by homogenizing the tissue in a low-salt buffer followed by treatment of the homogenate with proteinase K to degrade unwanted protein and ethanol to precipitate total nucleic acid. The mRNA was then separated on an oligo (dT) cellulose column. Confirmation that the mRNA was highly active in directing protein synthesis was shown by the incorporation of 35S-methionine into labelled products. Amongst the synthesized products is material which co-elates with FVIIIR:Ag as shown by radioactive and activity peaks. Further detailed studies are being undertaken to confirm immunological identity of this material with porcine factor VIII. The advantages of this technique to the study of the molecular characteristics of factor VIII and other clotting factors will be discussed.